Teachers as Curriculum Evaluator: The Implementation of Authentic Assessment in Curriculum 2013 by English Teacher - Ade Windiana Argina (Humanitatis : Journal of Language and Literature, 2017)
Authentic assessment becomes a crucial impression in its implementation in which teachers should comprehensively implement it in every teaching and learning process. The curriculum implementation needs some supporting factors including teachers' familiarity of the curriculum being implemented and their professional competence (Lengkanawati, 2004). However, a number of teachers still have lack understanding about the concept of authentic assessment impacting its implementation. 1) How comprehensively this assessment has been implemented by teachers (tools mostly used, aspect mostly assessed and the level of comprehensiveness of its implementation)? and 2) what problems are encountered by teachers? By employing mixed-method, this study revealed that less than 40% teachers have comprehensively implemented this assessment and most of them still face difficulties in implementing authentic assessment: lack of comprehensive knowledge and understanding about authentic assessment, their low readiness, low support and cooperation from stakeholders and time limitation. Hopefully, this study can be used as a scientific reflection and information for teachers and stakeholders to improve the quality of curriculum implementation.